Review of the effects of Task-based Language Teaching on EFL learners’ speaking performance: What remains to be researched? - Truong Sang Huynh; Van Loi Nguyen (CTU Journal of Innovation and Sustainable Development)
Given the research trend on task-based language teaching (TBLT), several reviews have been conducted on its effects. However, no review has explored specific skills. This study aims to review previous studies with a focus on the improvement of EFL learners’ speaking performance. The main purpose is to reveal a gap for future study. Using the systematic review approach, we selected 25 qualified studies from different databases. Results showed that TBLT implementation promoted both general speaking and speaking components (i.e., complexity, accuracy, and fluency). Most of the studies either employed or adapted Willis’ model. The present study suggests that future research could explore the comparative effects of various task-based methodological options. Moreover, the text-driven approach to task design and implementation can be further researched to enhance EFL learners’ engagement and speaking performance.